2018
DOI: 10.1002/advs.201800240
|View full text |Cite
|
Sign up to set email alerts
|

Multimeric Amphipathic α‐Helical Sequences for Rapid and Efficient Intracellular Protein Transport at Nanomolar Concentrations

Abstract: An amphipathic leucine (L) and lysine (K)‐rich α‐helical peptide is multimerized based on helix‐loop‐helix structures to maximize the penetrating activities. The multimeric LK‐based cell penetrating peptides (LK‐CPPs) can penetrate cells as protein‐fused forms at 100–1000‐fold lower concentrations than Tat peptide. The enhanced penetrating activity is increased through multimerization by degrees up to the tetramer level. The multimeric LK‐CPPs show rapid cell penetration through macropinocytosis at low nanomol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 62 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…The rapid and efficient cellular upake of the LK-BATrism could facilitate the generation of a larger temperature increase upon laser irradiation compared to bare probes at such lower concentrations. Furthermore, we compared the activity of the LK peptide with a well-known CPP, the TAT sequence, ,, on the enhancement of cellular uptake of the nanoprobes (Figure S12). The LK-BATrism showed significantly higher cell internalization than the TAT-BATrisms, supporting the superior activity of LK-based cell penetration.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rapid and efficient cellular upake of the LK-BATrism could facilitate the generation of a larger temperature increase upon laser irradiation compared to bare probes at such lower concentrations. Furthermore, we compared the activity of the LK peptide with a well-known CPP, the TAT sequence, ,, on the enhancement of cellular uptake of the nanoprobes (Figure S12). The LK-BATrism showed significantly higher cell internalization than the TAT-BATrisms, supporting the superior activity of LK-based cell penetration.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In a previous study, LK peptides showed a higher cellular uptake efficiency than other commonly used CPPs. 26,27 Therefore, conjugation of LK peptides on the BATrisms will allow the use of a low probe dose and low laser power with proper modification of these peptides to the particles by efficiently increasing cellular accumulation. The amino acid sequence and characterization of the peptides used in this study are listed in Table S2 and Figure S7, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, cationic CPPs present problems, such as their inability to selectively home to the target. To improve the performance of CPPs-based PDCs, recently, a study found that multimers of lysine (K) and leucine (L) of the amphiphilic α-helical LK sequence can penetrate cells at the nanomolar level, which was 100–1000 folds lower than the transverse concentration of traditional CPPs [ 86 ]. The stronger the interaction between CPPs and cell surface receptors, the faster the PDCs enter the tumor cells [ 87 , 88 ].…”
Section: Categories Of Drug Conjugatesmentioning
confidence: 99%
“…[107] The anisotropic morphology and rough surface of BATrisms allowed the PICs to exhibit a promising PTT conversion efficiency (~86%) by enhancing the electromagnetic field. Efficient delivery of PICs into tumor cells was achieved by the conjugation of a cell-penetrating peptide, [108,109] the leucine-and lysine-rich peptide (LK peptide, LKKLLKLLKKLLKLGGLKKLLKLLKKLLKLAG), to the surface of BATrisms. Based on these merits, the PICs demonstrated antitumor efficacy with a very small dose (2.5 μg Au) under very low laser intensity (808 nm, 0.25 W/cm 2 ).…”
Section: Peptide-inorganic Conjugatesmentioning
confidence: 99%